The impact of network-related practices on HR processes - Kaynatan, Katya Selin; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The following thesis will investigate the impact of referral-based hiring and network-oriented HR practices on discrimination against individuals outside of established networks. It will examine how networking affects recruitment, the potential consequences for companies, and where these practices may cause discrimination. The study will employ a mixed-methods approach involving a questionnaire and semi-structured interviews with employee and company representatives. The findings suggest that even though referral-based hiring can provide advantages to job seekers, it does not guarantee success, and companies should strive for inclusive and equitable hiring practices. Contributing to the ongoing discussion about the impact of network-related practices on HR processes, the research will also highlight the importance of considering the broader context of network-oriented HR practices in fostering a diverse and inclusive workplace.
Vedoucí práce: Kateřina Legnerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses